Pengaruh Penggunaan QRIS Terhadap Kepuasan Pengguna Dikalangan Universitas Muhammadiyah Makassar Ditinjau Dalam Perspektif Ekonomi Islam - Sampurwati, Selina; Salim, Agus; Wahyuni, Sri (IAIN Kendari, 2025)
This study aims to analyze the impact of QRIS (Quick Response Code Indonesia Standard) usage on user satisfaction among students at Universitas Muhammadiyah Makassar, viewed from the perspective of Islamic economics. With the rapid development of information technology, QRIS is expected to enhance the efficiency of financial transactions. The research method used is a quantitative survey, collecting data through questionnaires distributed to 99 respondents. The results indicate that QRIS usage has a positive and significant effect on user satisfaction, with ease of use, transaction speed, and security being the main factors influencing satisfaction. This research is expected to contribute to the development of better digital payment systems that align with the principles of Islamic economics.